Schwann Cell-Derived CCL2 Promotes the Perineural Invasion of Cervical Cancer - Huang, Ting; Fan, Qiong; Wang, Yiwei; Cui, Yunxia; Wang, Zhihua; Yang, Linlin; Sun, Xiao; Wang, Yudong (Frontiers in Oncology, 2020)
Perineural invasion (PNI) has guiding significances for nerve preservation in cervical cancer, but there is no definite marker indicating PNI. Two cervical cancer cell lines (HeLa and ME-180) showed significant abilities to migrate along neurites in vitro and in vivo. Morphological observation revealed that Schwann cells (SC) arrived at the sites of cervical cancer cells before the onset of cancer metastasis. We used high-throughput antibody array to screen the signals mediating the interaction of nerve cells and cancer cells and found the high expression of CCL2 in dorsal root ganglion (DRG). Meanwhile, serum CCL2 showed a notable raise especially in cervical adenocarcinoma. SC-derived CCL2 bound to its receptor CCR2 and promoted the proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) of cervical cancer cells. In turn, cancer cell-derived signals triggered the expression of metalloproteinases (MMPs) including MMP2, MMP9 and MMP12 in SCs, promoting SCs to dissolve matrix. These data demonstrated that the cancer-nerve crosstalk formed a tumor microenvironment (TME) that facilitated to PNI. We identified the CCL2/CCR2 axis as a potential marker to predict the PNI and affect the nerve preservation for cervical cancer.